PENGOLAHAN DATA SEISMIK 2D MARINE MENGGUNAKAN ProMAX DI AREA TENGGARA PULAU SIMEULUE - Jamaluddin Jamaluddin; Johanes Gedo Sea; Fitriani Fitriani; Maria Maria (PETROGAS: Journal of Energy and Technology, 2020)
Multiple in marine seismic data is the noise formed due to the high impedance contrast at the boundary between layer. Multiple interferes the data processing that will also affect the interpretation of subsurface image. The use of seismic reflection in ocean has become an activity that is often performed with a variety of purposes, to map the subsurface. The basic objective of seismic data processing is to convert the recorded information from the field into data that can be interpreted. One goal of seismic data processing is to eliminate or reduce the noise of reverberation and multiples as well as enhance the signal to noise ratio. The data are a 2D marine reflection seismic data with SEG-Y format that will be processed with using ProMAX software. SEG-Y data are combined with field geometry data in processing of header load, then is carried out noise reduction (trace editing and filtering), and seismic signal amplification (deconvolution and TAR).